A Mobility Enabled Inpatient Monitoring System Using a ZigBee Medical Sensor Network - Hoi Ching Tung; Kim Fung Tsang; Ka Lun Lam; Hoi Yan Tung; Benjamin Yee Shing Li; Lam Fat Yeung; King Tim Ko; Wing Hong Lau; Veselin Rakocevic (Sensors, 2014)
This paper presents a ZigBee In-Patient Monitoring system embedded with a new ZigBee mobility management solution. The system enables ZigBee device mobility in a fixed ZigBee network. The usage, the architecture and the mobility framework are discussed in details in the paper. The evaluation shows that the new algorithm offers a good efficiency, resulting in a low management cost. In addition, the system can save lives by providing a panic button and can be used as a location tracking service. A case study focused on the Princes of Wales Hospital in Hong Kong is presented and findings are given. This investigation reveals that the developed mobile solutions offer promising value-added services for many potential ZigBee applications.